2019
DOI: 10.9734/jeai/2019/v41i330401
|View full text |Cite
|
Sign up to set email alerts
|

Path Coefficient Analysis of Some Prominent Agronomic Traits in Castor (Ricinus communis L.) Germplasm

Abstract: Background and Objective: Castor (Ricinus communis L.) is a diploid plant with chromosome number of 2n=20 which belongs to family of Euphorbiaceous and genus Ricinus.  Correlation alone is not efficient for variability studies. So, it should be in conjugation with Path co- efficient analysis to know the direct and indirect effects. This study was conducted to assess the role of evaluating path coefficient analysis in castor. Materials and Methods: A Field experiment was carried out to determine direct an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Many studies have reported positive and significant correlations among seed yield, height at flowering, number of racemes per plant, raceme length, number of capsules per raceme, and 100 seed weight (Mullualem Atinafu et al, 2019; Ramesh & Venkate, 2001). The seed weight observed in the present study was in accordance with other studies, such as Goodarzi et al (2015), who reported that the 10‐seed weight on the primary raceme varied from 2.1 to 3.3 g, whereas Bhardwaj et al (1996) reported a 100‐seed weight variable ranged from 10 to 44 g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported positive and significant correlations among seed yield, height at flowering, number of racemes per plant, raceme length, number of capsules per raceme, and 100 seed weight (Mullualem Atinafu et al, 2019; Ramesh & Venkate, 2001). The seed weight observed in the present study was in accordance with other studies, such as Goodarzi et al (2015), who reported that the 10‐seed weight on the primary raceme varied from 2.1 to 3.3 g, whereas Bhardwaj et al (1996) reported a 100‐seed weight variable ranged from 10 to 44 g.…”
Section: Discussionmentioning
confidence: 99%
“…Among the fungal pretreated thesis, I. lacteus showed the highest BMY per hectare (75.80 and 144.5 m 3 CH 4 ha −1 for N0 and N120, respectively) while P. ostreatus reached values of 54.29 for N0 and 129.8 m 3 CH 4 ha −1 for N120 (Figure 9). Many studies have reported positive significant correlations among seed yield, height at flowering, number of racemes per plant, raceme length, number of capsules per raceme, and 100 seed weight (Mullualem Atinafu et al, 2019;Ramesh & Venkate, 2001). The seed weight observed in the present study was in accordance with other studies, such as Goodarzi et al (2015), who reported that the 10-seed weight on the primary raceme varied from 2.1 to 3.3 g, whereas Bhardwaj et al (1996) reported a 100-seed weight variable ranged from 10 to 44 g. The increase in nitrogen dose significantly affected the main yield contributing traits, such as the number of secondary racemes, number of capsules per raceme for both primary and secondary racemes, and seed weight of primary raceme.…”
Section: Biomethane Yield Per Hectarementioning
confidence: 99%